CD160-Associated CD8 T-Cell Functional Impairment Is Independent of PD-1 Expression - Viganò, Selena (Public Library of Science, 2014)
Expression of co-inhibitory molecules is generally associated with T-cell dysfunction in chronic viral infections such as HIV or HCV. However, their relative contribution in the T-cell impairment remains unclear. In the present study, we have evaluated the impact of the expression of co-inhibitory molecules such as 2B4, PD-1 and CD160 on the functions of CD8 T-cells specific to influenza, EBV and CMV. We show that CD8 T-cell populations expressing CD160, but not PD-1, had reduced proliferation capacity and perforin expression, thus indicating that the functional impairment in CD160(+) CD8 T cells may be independent of PD-1 expression. The blockade of CD160/CD160-ligand interaction restored CD8 T-cell proliferation capacity, and the extent of restoration directly correlated with the ex vivo proportion of CD160(+) CD8 T cells suggesting that CD160 negatively regulates TCR-mediated signaling. Furthermore, CD160 expression was not up-regulated upon T-cell activation or proliferation as compared to PD-1. Taken together, these results provide evidence that CD160-associated CD8 T-cell functional impairment is independent of PD-1 expression.